Comprehensive Study of an Attitude of Medical Professionals Towards Organ Donation in Russia. (July 2018) - Reznik, Oleg; Popova, Olga; Skvortsov, Andrey; Tischenko, Pavel; Reznik, Alexander
Abstract : Introduction: One of the main reasons for organ shortage is the discrepancy between scientific progress in the field of transplantation and lack of knowledge of the problems associated with deceased donation by both ordinary people and members of medical society. It is clearly shown in the reports on the attitude of towards the problem of organ donation. Materials and Methods: We conducted a comprehensive study to evaluate knowledge level and attitudes of medical personnel involved in resuscitation procedures and counseling services to patients with severe brain injuries and diseases and in the deceased organ donation protocols by anonymous questionnaires. The study involved 70 neurologists, 105 intensivist and 118 nurses of intensive care units, a total of 293 people. Results: When analyzing the data obtained during the survey, conflicting trends were determined. Among neurologists, almost 80% are aware of the existence of the law of transplantation, 59% - about instructions for diagnosing brain death. At the same time 81% of neurologists know the basic criteria of brain death. Under the supervision of 63% of neurologists, there were ever patients with suspected brain death. But, at the same time, 83% of neurologists have never had to work with donation team (OPO). 46% of neurologists could consider organ procurement from deceased donor to be routine practice and, in turn, 82% of intensivists consider deceased donation a routine, which is 1.7 times higher than the same indicator of a survey among neurologists. In general, answers to questions are more positive in intensivists than in neurologists. In the questionnaire of nurses, almost half of the respondents were ready to become organ donors, which indicated their high confidence in transplantation programs. Two-thirds of the interviewed among the hospital employees who are involved in donors consider it necessary to pay for participation in donor programs and the introduction of a paid position of the transplant coordinator. Conclusions: A study of the position of medical personnel in relation to problems of organ donation showed a low awareness of neurologists, in contrast to intensivists, which requires the finalization of training programs of this category of doctors. Thus, the unsatisfactory readiness of neurologists for diagnosing brain death is one of the causes of the deficit of deceased donors among those who died from cerebrovascular diseases. Given the high percentage of trust in transplantation programs from medical personnel, the next step is to conduct a study of St. Petersburg residents about their willingness to participate in donor programms. The abstract has been prepared with the financial support of the Russian Science Foundation, Project No. 17-18-01444.